Les procédés contemporains de mise en scène des guerres - Dominique Trouche (Amnis)
The spreading of the communication forms within the memorial sites of the world wars appears in terms of visual strategies and theatrical production. The relationship to space is modified, the places of remembrance are interconnected. Such processes are also used in the transformation of the exposure medium. Scenographic techniques intermingle with theatrical and cinematographic ones thus contributing to make it an audio-visual work of art. This process directly affects the representations of the dead and represents significant changes, as they become the victims and no longer the heroes of the war.